Structural characteristics, functions, and counteracting strategies of biofilms in Staphylococcus aureus - Yanze Xia; Zhenghui Hu; Qiyuan Jin; Qi Chen; Chenhao Zhao; Rui Qiang; Zonggang Xie; Liubing Li; Haifang Zhang (Computational and Structural Biotechnology Journal)
Background: Staphylococcus aureus (S. aureus) is a prevalent pathogen associated with a wide range of infections, exhibiting significant antibiotic resistance and posing therapeutic challenges in clinical settings. The formation of biofilms contributes to the emergence of resistant strains, further diminishing the efficacy of antibiotics. This, in turn, leads to chronic and recurrent infections, ultimately increasing the healthcare burden. Consequently, preventing and eliminating biofilms has become a critical focus in clinical management and research. Aim of review: This review systematically examines the mechanisms underlying biofilm formation in S. aureus and its contribution to antibiotic resistance, emphasizing the essential roles biofilms play in maintaining structural integrity and enhancing resistance. It also analyses the protective mechanisms that fortify S. aureus biofilms against antimicrobial treatments. Furthermore, the review provides a comprehensive overview of recent therapeutic innovations, including enzymatic therapy, nanotechnology, gene editing, and phage therapy. Key scientific concepts of review: Emerging therapeutic strategies present novel approaches to combat S. aureus biofilm-associated infections through various mechanisms. This review discusses recent advancements in these therapies, their practical challenges in clinical application, and provides an in-depth analysis of each strategy’s mechanisms and therapeutic potential. By mapping future research directions, this review aims to refine anti-biofilm strategies to control infection progression and effectively mitigate recurrence.